EFEKTIVITAS METODE SPEOS (STIMULASI PIJAT ENDORPHIN, OKSITOSIN & SUGESTIF) TERHADAP KELANCARAN ASI PADA IBU NIFAS DI PMB DENIK (RUMAH ALODEA)PARE - walu, martina; susanti, silfia (Jurnal Ilmu Kebidanan, 2024)
The success of breastfeeding is caused by decreased stimulation of the hormone oxytocin, so postpartum mothers have excessive worry about breastfeeding. The purpose of this study was to determine the effectiveness of the SPEOS method on the smoothness of breast milk in postpartum mothers in PMB Denik (Alodea House) Pare. Researchers use a pre-experimental design with a one group pretest – posttest design approach. The study population was all postpartum mothers in PMB Denik Tertek Pare with a total sample of 20 people using total sampling techniques. The breastfeeding smoothness instrument uses questionnaires, while the SPEOS intervention method uses standard operating procedures (SOPs). The analysis used paired sample t test. Fluency of breast milk from 20 respondents showed data that before the SPOES method most respondents had a current category of 11 (55%) and after the SPOES method all respondents had a current category of 20 (100%). Analysis of the paired sample t test shows a value of ρ (0.000) < α 0.05, which means that there is an effectiveness of the SPEOS method on the smoothness of breast milk in postpartum mothers at PMB Midwife Denik 9Alodea House) Pare. The SPEOS method in postpartum mothers helps improve the smoothness of breast milk discharge and builds a positive self-concept through suggestiveness, so that mothers are confident that they can provide smooth breastfeeding.